2021
DOI: 10.17977/um001v6i32021p112-120
|View full text |Cite
|
Sign up to set email alerts
|

College Students’ Academic Procrastination during the Covid-19 Pandemic: Focusing on Academic Achievement

Abstract: This research aims to describe the level of college students’ academic procrastination, analyze differences in academic procrastination among the college students, and analyze the relationship between academic procrastination and academic achievement. This research uses a quantitative method with a survey and correlational design. The research population is 620 Sekolah Tinggi Keguruan dan Ilmu Pendidikan Singkawang (STKIP) Singkawang college students. The sample is taken using a simple random sampling techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…This means that there is no direct correlation between self-concept and learning achievement. This result is in line with the results of previous studies which stated that there was no positive relationship between learning achievement and self-concept (Awai & Ogori, 2016;Basith et al, 2021;Juliyanti & Pujiastuti, 2020;Yengimolki, et al, 2015). By inference, the results of the analysis stated that there was a very weak and insignificant positive relationship between self-concept and learning achievement.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This means that there is no direct correlation between self-concept and learning achievement. This result is in line with the results of previous studies which stated that there was no positive relationship between learning achievement and self-concept (Awai & Ogori, 2016;Basith et al, 2021;Juliyanti & Pujiastuti, 2020;Yengimolki, et al, 2015). By inference, the results of the analysis stated that there was a very weak and insignificant positive relationship between self-concept and learning achievement.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, if the self-concept is low, the learning outcomes are low. However, several studies also explain that there is no strong correlation between academic achievement and self-concept (Awai & Ogori, 2016;Basith et al, 2021;Juliyanti & Pujiastuti, 2020;Yengimolki, et al, 2015). These results show that there is still a debate about the correlation between self-concept and learning achievement.…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…The authors are aware that it will be necessary to balance the number of participants for gender in the next researches with regard to these topics for examining the differences between males and females in procrastination (confirmed by Mandap, 2016;Ozer, Demir & Ferrari, 2009), decision-making styles (as in Bajwa, et al, 2016), and intolerance of uncertainty (for instance, in Dugas, et al, 2001). For example, as reported by Mandap (2016) and Basith (2021), male university students tend to procrastinate more than the female ones. As well as, Bajwa (2016) found that females use more rational decision-making style and show more intuitive decision-making ability than males.…”
Section: Limitations and Conclusionmentioning
confidence: 79%
“…In the past few years, most studies investigating the impact of COVID-19 on the educational system focused mainly on students' mental health (e.g., Bayham and Fenichel, 2020;Viner et al, 2020;Pfefferbaum, 2021), or academic achievement (e.g., Kuhfeld et al, 2020;Basith et al, 2021). In contrast, the financial security of students during the pandemic was rarely investigated (Kee, 2021;Walsh et al, 2021).…”
Section: Open Access Edited Bymentioning
confidence: 99%